Literacy and technology program to enhance the potential of the youth of Mira village through community empowerment - Hernita Pasongli; Wilda Syam Tonra; Dahlan Wahyudi; Marwis Aswan; Winda Syam Tonra (LP2M Universitas Islam Negeri Mataram, 2024)
[Bahasa]: Pendidikan di Desa Mira, Kecamatan Morotai Timur Kabupaten Pulau Morotai, Provinsi Maluku Utara masih tertinggal dibandingkan desa-desa lainnya di wilayah sekitar. Kurangnya fasilitas perpustakaan sekolah dan sarana teknologi informasi di desa tersebut mengakibatkan rendahnya literasi dan penguasaan teknologi masyarakat setempat. Di sisi lain, literasi dan teknologi merupakan unsur penting untuk menghadapai tantangan globalisasi. Pengabdian kepada masyarakat ini bertujuan untuk meningkatkan pengetahuan dan penguasaan teknologi masyarakat Desa Mira melalui program literasi dan teknologi dalam bentuk pelatihan pembuatan konten video. Program pengabdian kepada Masyarakat ini dilaksanakan selama 2 bulan oleh tim yang terdiri dari 19 mahasiswa dan 3 dosen dari Program Studi Pendidikan Matematika Universitas Khairun melalui program pemberdayaan masyarakat oleh mahasiswa (PMM) yang didanai oleh Kementerian Pendidikan, Kebudayaan, Riset dan Teknologi Tahun Anggaran 2023. Partisipan program ini adalah siswa-siswa pada sekolah Madrasah Tsanawiyah (MTs) Makharimal Akhlak Mira. Tahapan pengabdian kepada masyarakat ini meliputi tahap persiapan, sosialisasi, pelaksanaan, dan evaluasi. Aktivitas penguatan literasi dilakukan melalui pengajaran baca tulis dan membaca dongeng bersama. Sementara penguatan penguasaan teknologi dilakukan melalui pelatihan pembuatan konten video menggunakan aplikasi Capcut dan Kinemaster yang hasilnya diupload di akun YouTube. Hasil pengabdian kepada masyarakat ini menunjukkan adanya peningkatan kemampuan literasi dan penguasaan teknologi dalam bidang pembuatan konten video pada siswa sekolah MTs Makharimal Akhlak Mira. Kata Kunci: literasi, siswa madrasah, teknologi, konten video [English]: Education in Mira Village, East Morotai District, Morotai Island Regency, North Maluku Province, is still underdeveloped compared to other villages in the surrounding area. The lack of a school library and information technology facilities in the village has resulted in low literacy and poor technology mastery in the local community. On the other hand, literacy and technology are important elements to face the challenges of globalization. This community service aims to improve the knowledge and mastery of technology of the Mira Village community through literacy and technology programs in the form of video content creation training. This community service program was carried out for 2 months by a team of 19 students and 3 lecturers from the Mathematics Education Department of Khairun University through a community empowerment program by students (PMM) funded by the Ministry of Education, Culture, Research, and Technology. The participants of this program were students at Madrasah Tsanawiyah (MTs) Makharimal Akhlak Mira school. The stages of this community service include preparation, socialization, implementation, and evaluation. Literacy-strengthening activities are carried out through training in reading and writing and reading fairy tales together. Meanwhile, strengthening mastery of technology is done through training in video content creation using the Capcut and Kinemaster applications, the results of which are uploaded to a YouTube account. The results of this community service show an increase in literacy skills and mastery of technology in video content creation for MTs Makharimal Akhlak Mira school students. Keywords: literacy, madrasa students, technology, video content